PENDIDIKAN MULTIPLE INTELLIGENCES PADA ANAK USIA DINI - Sulfa Nurrachma (Universitas Khairun, 2015)
Programs such as education and learning that took place at this time , therefore, must be directed or oriented to individual learners . The fact shows that the educational program of the present day more done by making a generalization of the potential and abilities of students . Multiple intelligences can use for teaching in early childhood education. It cover integrated learning without separated others. Teacher can teach them by using some approaches. UsingÂ Multiple Intelligences in early childhood shows the competences of students. The parents can guide their children with focusing on childrenâ€™s competences.